2016
DOI: 10.3762/bjoc.12.208
|View full text |Cite
|
Sign up to set email alerts
|

Diels–Alder reactions in confined spaces: the influence of catalyst structure and the nature of active sites for the retro-Diels–Alder reaction

Abstract: SummaryDiels–Alder cycloaddition between cyclopentadiene and p-benzoquinone has been studied in the confined space of a pure silica zeolite Beta and the impact on reaction rate due to the concentration effect within the pore and diffusion limitations are discussed. Introduction of Lewis or Brønsted acid sites on the walls of the zeolite strongly increases the reaction rate. However, contrary to what occurs with mesoporous molecular sieves (MCM-41), Beta zeolite does not catalyse the retro-Diels–Alder reaction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…By forming a complex with the dienophile, the LUMO is stabilized which reduces its energy gap with the HOMO of the diene, lowering the energy barrier which favours the Diels-Alder reaction more than the uncatalyzed reaction. Heterogenous catalysis of the Diels-Alder reaction has also been reported, where porous silica with active sites doped with catalytic metals [23]. Alternatively, the Diels-Alder reaction rate can be increased by raising the pressure [24].…”
Section: Introductionmentioning
confidence: 99%
“…By forming a complex with the dienophile, the LUMO is stabilized which reduces its energy gap with the HOMO of the diene, lowering the energy barrier which favours the Diels-Alder reaction more than the uncatalyzed reaction. Heterogenous catalysis of the Diels-Alder reaction has also been reported, where porous silica with active sites doped with catalytic metals [23]. Alternatively, the Diels-Alder reaction rate can be increased by raising the pressure [24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the effects on porosity of HCPs are significant, but almost all investigations focused on the role of monomer length and geometry on the porosity [6,1932]. Researchers have synthesized a series of carbazole-based microporous HCPs and came to the conclusion that 2D and 3D-conjugated architectures with nonplanar rigid conformation and dendritic building blocks were favorable for getting a high BET specific surface area [6,1921 2325].…”
Section: Introductionmentioning
confidence: 99%
“…Qiao synthesized five microporous materials using carbazole with different flexible chains, proving that the flexible chain length was an important factor for the porosity [26]. Different phenyl-based structures were also synthesized to explore the effect of the monomer structure on the porosity [2732]. However, researchers seldom cared about the effect of reaction conditions on the porosity, which is of far-reaching significance in preparation of HCPs.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the effects on porous properties of HCPs is significant, but almost all the reported focused on the role of monomer length and geometry on porous structure [6,[16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Han has made a series of carbazole-based microporous polymers, reached the conclusion that 2D and 3D conjugated architectures with non-planar rigid conformation and dendritic building blocks is favorable for getting high BET specific surface area [6,[16][17][18][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Qiao synthesized five microporous materials using carbazole with different flexible chain, proving that the flexible chain length is an important factor on the porous properties [23]. Different phenyl-based structures are also synthesized to explore the monomer structure effect on the porosity [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%